PENDAMPINGAN BELAJAR ANAK USIA DINI DI ERA PANDEMI COVID-19 - Fierda Nurany; Hernaldi Kesastriawan Sugandi; Avista Sridevi Putri Anarys (Politeknik Negeri Sriwijaya, 2021)
This research has a purpose to knowing the education during the pandemic. This community service was carried out to provide assistance to the situation experienced by kindergarten teachers in the sudden change of the learning modes due to the Covid-19 pandemic. fEducation fis fthe fmost importantf fthing fthat wilfl fbe so useful for our life, every human needs education to make their life be a better life. But the most important thing among it, is a good moral that we have to build into the character of the kids. This research using the descriptive method that using quantitative support by random sampling techniques in the selection of research subjects, in order to obtain 30 student respondents from Dharma Wanita Kindergarten, Sepanjang. The results showed that the average acquisition of character education was 46% with the category starting to develop.